Body image and risk for development of eating disorders in Nutrition and Physical Education students (Research, Society and Development, 2022)
Body image dissatisfaction, the prevalence of extreme body shapes and weight control behaviors are increasing among college students of both sexes. Although they are still more frequent in female students, young people and in university education. Investigations show a high prevalence of these behaviors in students in the health field, especially in Nutrition and Physical Education. This study aimed to evaluate body image and the risk of developing eating disorders in Nutrition and Physical Education students from a private higher education institution in the State of Alagoas, raising the issue in the academic community. It was a cross-sectional study, exploratory and descriptive, in which the intention was to recruit all students duly enrolled in the initial and final periods of the Nutrition and Physical Education courses, in the period between 2019.2 and 2020.1. 86 participants were included, 25 (29.06%) of whom were male and 61 (70.93%) were female. The students of Nutrition courses started graduation with a greater tendency towards dysfunctional eating behavior and greater image distortion, decreasing over the years of graduation; among undergraduates in Physical Education, the opposite occurred, with a greater risk of image distortion and eating disorders in students at the end of the course, which can be considered a worrying phenomenon.